2006
DOI: 10.1055/s-2006-939925
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Cluster Headache

Abstract: Cluster headache is an uncommon yet distinctive neurovascular syndrome occurring in either episodic or chronic patterns. The most unique feature of cluster headache is the unmistakable circadian and circannual periodicity. The attacks are stereotypical, that is, of extreme intensity, of short duration, occurring unilaterally, and associated with robust signs and symptoms of autonomic dysfunction. Unlike migraine, during an attack the patient with cluster headache often paces about. Attacks frequently occur at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 125 publications
(211 reference statements)
0
25
0
Order By: Relevance
“…Most clinicians consider verapamil the preventative therapy of choice for both episodic and chronic cluster headache, 11 hence why it was chosen for prophylaxis. Corticosteroids (prednisone and dexamethasone) are the most rapidly acting prophylactic agents for cluster headache 12 but avoided for this patient given her known adrenal failure. The combination of autonomic symptoms with neuralgiform pain closely related to SUNCT was the rationale for utilizing carbamazepine as this has been shown to have some partial effect in patients with SUNCT.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinicians consider verapamil the preventative therapy of choice for both episodic and chronic cluster headache, 11 hence why it was chosen for prophylaxis. Corticosteroids (prednisone and dexamethasone) are the most rapidly acting prophylactic agents for cluster headache 12 but avoided for this patient given her known adrenal failure. The combination of autonomic symptoms with neuralgiform pain closely related to SUNCT was the rationale for utilizing carbamazepine as this has been shown to have some partial effect in patients with SUNCT.…”
Section: Discussionmentioning
confidence: 99%
“…Verapamil, an L-type CCB, has been used widely in clinical practice to treat hypertension [10], cardiac arrhythmias [11], cluster headaches [12], and migraines [13], but not to lower blood glucose for diabetes. Since the previous evidence of a hypoglycemic effect of verapamil comes from animal studies, there are few data in humans that can be compared with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The good response to corticosteroids in CH, described in many articles [18,19], remains to be clarified in further studies. Earlier studies have shown that one of many effects of corticosteroids is to suppress spontaneous interleukin 2 (IL‐2) release [20,21].…”
Section: Discussionmentioning
confidence: 99%